PERENCANAAN SPASIAL DAN STRATEGI PENINGKATAN HASIL PRODUKSI BENIH JAGUNG HIBRIDA DI KABUPATEN BONE - sumarni panikkai; Wahyu Hidayat; Bahtiar - (JURNAL MANAJEMEN AGRIBISNIS, 2019)
Bone Regency has great potential as a pioneer of hybrid specialty corn seed producers in eastern Indonesia. This potential is a regional advantage that will increasingly develop utilizing natural resources and the environment in accordance with the conditions of corn farming. Corn is a food crop commodity that has a role in the development of Indonesia's agricultural economy which has a commodity of maize having multipurpose functions (4F), namely for food (food), feed (feed), fuel (fuel), and industrial raw materials (fiber) . Therefore, to achieve this situation, information is needed related to regional development planning so that it is expected to create sustainable agricultural development. The purpose of this study is to provide spatial data for locations that are suitable for corn plant development planning and information on strategies for increasing corn crop yield. The specific objectives of the study are: 1. Analyzing the suitability of the land with the carrying capacity of the land (the ability of the kahan) to plan the development of corn plants. 2. Creating a Strategy to Increase Production Results. The method used in this research is land carrying capacity and descriptive. The research locations were Ajangale District, Amali District and Dua Boccoe District Bone Regency. The results of this study, there are 42 villages that are suitable for the development of maize plants that are presented in land suitability based on land carrying capacity and Regional Spatial Planning (RTRW). Strategy to increase yields of maize production by piloting a Farmer-based Corporation project.